Pengaruh Kebijakan Dividen, Profitabilitas, Likuiditas, Pertumbuhan Perusahaan dan Ukuran perusahaan Terhadap Kebijakan Hutang (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2019 - 2022) - Syafi, Ahmad; Salim, Muhammad Agus; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The aim of this research is to reveal the influence of dividend policy, profitability, liquidity, company growth and company size on debt policy in the manufacturing industry listed on the Indonesia Stock Exchange (BEI) from 2019 to 2022. Dividend policy is measured by the dividend payout ratio, profitability is measured by return on assets, liquidity is measured by the current ratio, and company growth is measured by the ratio of total assets in year n to total assets in year n-1. and company size as measured by LN (total assets). This type of research is quantitative research. This research sample was obtained according to the criteria determined based on the purposive sampling method. From 2019 to 2022, 48 samples were collected from manufacturing companies listed on the Indonesian Stock Exchange. Multiple regression analysis will be used as the analysis method. The results of the analysis show that dividend policy and company growth have no effect on debt policy, while profitability, liquidity and company size have a negative effect on debt policy.. Keywords: Divident Policy, Profitability, Liquidity, Company Growth, Company Size, Debt Policy